2008
DOI: 10.1152/jn.90809.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Modulation of Cutaneous Aδ Nociceptors During Inflammation

Abstract: Previous studies have demonstrated that locally administered cannabinoids attenuate allodynia and hyperalgesia through activation of peripheral cannabinoid receptors (CB(1) and CB(2)). However, it is currently unknown if cannabinoids alter the response properties of nociceptors. In the present study, correlative behavioral and in vivo electrophysiological studies were conducted to determine if peripheral administration of the cannabinoid receptor agonists arachidonyl-2'-chloroethylamide (ACEA) or (R)-(+)-metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 80 publications
3
25
0
Order By: Relevance
“…In other conditions, activation of cannabinoid receptors in the periphery reduces hyperalgesia after inflammation. 37,38 Importantly, we also observed strong expression of CB1 and CB2 receptors in the brain and spinal cord, and to a similar extent in younger and older hBERK1 and BERK mice (data not shown). This could contribute to the effectiveness of a relatively low dose of CP 55940, whereas a relatively higher dose of morphine is required because of the lower expression of MOR.…”
Section: Effect Of Morphine On Hyperalgesia In Mice Expressing Hbssupporting
confidence: 51%
“…In other conditions, activation of cannabinoid receptors in the periphery reduces hyperalgesia after inflammation. 37,38 Importantly, we also observed strong expression of CB1 and CB2 receptors in the brain and spinal cord, and to a similar extent in younger and older hBERK1 and BERK mice (data not shown). This could contribute to the effectiveness of a relatively low dose of CP 55940, whereas a relatively higher dose of morphine is required because of the lower expression of MOR.…”
Section: Effect Of Morphine On Hyperalgesia In Mice Expressing Hbssupporting
confidence: 51%
“…The idea that CB1 receptors reside on afferent nerve endings and that their activation there has analgesic actions is supported by several studies of both somatic and visceral pain. Subcutaneous intraplantar injection of cannabinoid agonists at the site of experimental inflammation suppressed pain responses [1, 14, 15, 20] and decreased the activation of cutaneous nerve fibers innervating inflamed skin [20]. In a model of interstitial cystitis pain, intravesical administration of a cannabinoid agonist also reduced the sensitization of bladder afferent nerves in a CB1-dependent manner [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, while Stander et al (2005) found CB1 receptor-expressing myelinated fibres, our samples apparently lacked such fibres in the skin. Interestingly, the CB1 receptor expressed by myelinated afferent fibres in the skin might not be in a responding configuration in naive conditions, as Potenzieri and colleagues (Potenzieri et al 2008) reported recently that CB1 receptor agonists reduce Aδ nociceptor activity only in inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%